Hypermutation In Pancreatic Cancer - Humphris, Jeremy L.; Patch, Ann-Marie; Nones, Katia; Bailey, Peter J.; Johns, Amber L.; Mckay, Skye; Chang, David K.; Miller, David K.; Pajic, Marina; Kassahn, Karin S.; Quinn, Michael C. J.; Bruxner, Timothy J. C.; et al. (Gastroenterology, 2017)
Pancreatic cancer is molecularly diverse, with few effective therapies. Increased mutation burden and defective DNA repair are associated with response to immune checkpoint inhibitors in several other cancer types. We interrogated 385 pancreatic cancer genomes to define hypermutation and its causes. Mutational signatures inferring defects in DNA repair were enriched in those with the highest mutation burdens. Mismatch repair deficiency was identified in 1% of tumors harboring different mechanisms of somatic inactivation of MLH1 and MSH2. Defining mutation load in individual pancreatic cancers and the optimal assay for patient selection may inform clinical trial design for immunotherapy in pancreatic cancer.
EVALuna2:15259